Dark clouds or silver linings? Knightian uncertainty and climate change - Yu-fu Chen; Michael Funke; Nicole Glanemann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper examines the impact of Knightian uncertainty upon optimal climate policy through the prism of a continuous-time real option modelling framework. We analytically determine optimal intertemporal climate policies under ambiguity. Additionally, numerical simulations are provided to illustrate the properties of the model. The results indicate that increasing Knightian uncertainty accelerates climate policy, i.e. policymakers become more reluctant to postpone the timing of climate policies into the future.
Keywords: C61; D81; Q54; 330; climate change; Knightian uncertainty; ê ambiguity; real options; Klimaschutz; Zeitverwendung; Entscheidung bei Unsicherheit; Klimaveränderung; Theorie